2009
DOI: 10.2320/matertrans.m2009035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heating Temperature on Interface Separation Behavior between Ti-20 mol% Al Alloy and High Carbon Steel

Abstract: Ti-20 mol% Al (Ti-12.3 mass% Al) alloy was diffusion-bonded to high carbon steel (0.82 mass% C) at 1273 K for 3.6 ks in a vacuum. The joint had a space of a few micrometers in thickness between the Ti-20 mol% Al alloy and the steel, and several specimens separated near the interface promptly after the bonding treatment. This phenomenon is referred to as 'interface separation'. This paper describes the influence of heating temperature on the interface separation. Diffusion bonding of the Ti-20 mol% Al alloy to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Considering the experimental results for the Ti-15Sn alloy/iron material and Ti-20Al alloy/iron material joints, [7][8][9] it is concluded that the interface separation is attributed to the preferential diffusion of iron into the titanium alloy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the experimental results for the Ti-15Sn alloy/iron material and Ti-20Al alloy/iron material joints, [7][8][9] it is concluded that the interface separation is attributed to the preferential diffusion of iron into the titanium alloy.…”
Section: Discussionmentioning
confidence: 99%
“…To encourage the effective use of these materials, they have been joined to themselves and other materials by various joining methods, such as diffusion bonding, 1,2) brazing, 3) friction welding, 4) and electron beam welding. 5) The authors have previously investigated the interfacial microstructures and the bonding strengths of Ti-Al alloy/iron material joints produced by diffusion bonding, [6][7][8][9] because steel is a dominant structural material in industrial products. It has been reported that, when Ti-20 mol% Al (Ti-20Al, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation